Ayala : the Philippinesʼ oldest business house - Lachica, Eduardo (Makati City, Philippines : Filipinas Foundations, Inc., 1984)
The Ayala story in fact, has been partly responsible for inspiring this broad and sweeping glance at the last 150 years of Philippine economic development.
The tally of 150 years -- The patriarchs as pioneers -- Exploring the world of Dona Margarita -- The proprietors as innovators -- Calatagan- visits to an enchanted country -- The heirs as working professionals -- The makati adventure -- Ayala in art -- Fernando Zobel: an artist as a painter, as a man.
Includes bibliographical references and index.
Keywords: CONGLOMERATE CORPORATIONS -- PHILIPPINES